Hepatic hydatidosis with great peritoneal growth.: Regarding one case. - Boudrandi, Sonia; Henderson, Eduardo; Ruso, Luis; Matteucci, Pablo; Perdomo, Roberto; Iade, Beatriz; Antoniello, Luis (Cirugía del Uruguay, 1989)
Authors present a case of non-complicated hepatic hydatidosis with great peritoneal growth. The interest is centered on the rarity of this presentation form; diagnostica! difficulties in spite of paraclinical advances, echography and tomography, and the need of a bibliographical revision on this gradually less frequent presentation form, and its successful treatment.